2009
DOI: 10.1007/s10531-009-9735-y
|View full text |Cite
|
Sign up to set email alerts
|

Marine biological community baselines in unimpacted tropical ecosystems: spatial and temporal analysis of reefs at Howland and Baker Islands

Abstract: Howland and Baker Islands are two small, isolated reef and sand islets located near the equator in the central Pacific Ocean that are situated approximately 60 km apart. In 2004 and 2006, species-level monitoring at multiple sites, coupled with towed-diver surveys in 2002, 2004, and 2006 on both of these federally protected islands, revealed diverse fish, coral, macroinvertebrate, and algal assemblages. This study examines interand intra-island spatial and temporal differences in community composition among si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
5
28
0
Order By: Relevance
“…This is consistent with patterns observed at other remote, often uninhabited, islands in the Pacific, including the US Phoenix Islands (Vroom et al, 2010) and parts of the Northwestern Hawaiian Islands (Vroom & Braun, 2010; Page-Albins et al, 2012). In contrast, more impacted reef communities, such as the populated islands of Kiritimati and Tabuaeran that neighbor Kingman and Palmyra, are typically characterized by a higher cover of fleshy turf and macroalgae (Sandin et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with patterns observed at other remote, often uninhabited, islands in the Pacific, including the US Phoenix Islands (Vroom et al, 2010) and parts of the Northwestern Hawaiian Islands (Vroom & Braun, 2010; Page-Albins et al, 2012). In contrast, more impacted reef communities, such as the populated islands of Kiritimati and Tabuaeran that neighbor Kingman and Palmyra, are typically characterized by a higher cover of fleshy turf and macroalgae (Sandin et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…These remote reefs lack local human impacts and are often characterized by high fish biomass (Williams et al, 2011c) and benthic communities dominated by hard corals and other calcifying (reef-building) organisms (Sandin et al, 2008; Vroom et al, 2010; Page-Albins et al, 2012). In the absence of local human impacts, intra-island variation in reef community organization is likely a result of natural variations in predation, competition for space, gradients in physical forcings such as light and wave energy, and disturbance events, such as storms (Hughes, 1989; Rogers, 1993; Hughes & Connell, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Smith (1992) found differences in macroalgal diversity among sites within a single island's intertidal habitat, and Zabin et al (2007b) found that intertidal species assemblages at bench sites were more similar to each other than to those found at cobble sites. Other studies on nearshore benthic communities have found that distributions or abundances of benthic organisms can vary with island habitat ( Vroom et al 2010), depth (Littler and Doty 1975), temperature (Cox and Smith 2011), and wave exposure (Bird 2006). We might expect similar findings for the benthic intertidal community.…”
Section: Spatial and Temporal Variation In Rocky Intertidal Communitimentioning
confidence: 99%
“…To date, most macroalgal stands in coral reef ecosystems have been reported in areas with limited herbivore activity (Mumby et al 2006, Wismer et al 2009) and/or areas where macroalgal distributions have been linked to declining water quality (De'ath & Fabricius 2010). However, it has also been suggested that macroalgal biomass is not necessarily influenced by human activity, but may be a natural characteristic of some coral reef ecosystems (Vroom et al 2006, Bruno et al 2009, Wismer et al 2009, Vroom et al 2010) and strongly related to coral cover (Williams et al 2001).…”
Section: Introductionmentioning
confidence: 99%